The Effect of Health Education by Peers on Knowledge and Attitude in Sexually Transmitted Diseases of Adolescents in High School I Subah Batang - Hartati Hartati; Moh Projo Angkasa; Sumarni Sumarni (Jurnal LINK, 2014)
Sexually transmitted diseases (STDs) are commonly called diseases that are transmitted through sexual intercourse. In Batang, the number of STD cases was 608 in 2010 and increased to be 1,296 in 2011. Most teenagers do not have accurate knowledge about reproductive health and sexuality. In addition, they have limited access to reproductive health information and services. Sources of this information are only from friends and/ or media, in which the information is usually inaccurate. The purpose of this study was to determine the effect of health education by peers to increase knowledge and change attitudes of adolescents in high school I Subah Batang. This research was quantitative, pre experimental design with One Group Pretest-Posttest. The population was young men and women class X and XI. The sample was 90 people, accounting for 15% of the population. This sample was divided into a group of 30 men and a group of 60 women. The results indicated that after providing health education by peers, 29 of male respondents (96.7%) and 60 of female respondents (100%) had a good level of knowledge. In addition, 21 of male respondents (70%) and 54 of female respondents (90%) had positive attitudes. Results of Wilcoxon Test Match Pair with a 95% confidence level (α = 0.05%) revealed differences in the level of knowledge of young men and women in class X and XI before and after given health education on sexually transmitted diseases (PMS) (ρ value = 0.001), and differences in the attitudes of young men and women in class X and XI before and after given the health education about sexually transmitted diseases (PMS). Health workers and high school educational institution I Subah were advised to further improve health education and provide counseling on sexually transmitted diseases (STDs) to train peers for distributing health education in order for people, especially adolescents of reproductive age to be able to prevent sexually transmitted diseases.